2018
DOI: 10.1002/esp.4492
|View full text |Cite
|
Sign up to set email alerts
|

Delta size and plant patchiness as controls on channel network organization in experimental deltas

Abstract: Understanding the feedbacks between water, sediment, and vegetation in deltas is an important part of understanding deltas as ecomorphodynamic systems. We conducted a set of laboratory experiments using alfalfa (Medicago sativa) as a proxy for delta vegetation to investigate: (1) the effects of plants on delta growth and channel network formation; and (2) the timescales controlling delta evolution in the presence of plants. Experiments were conducted with fluctuating discharge (i.e. flood and base flow periods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 77 publications
0
21
0
Order By: Relevance
“…This patch-scale feedback may strongly influence sediment retention on deltas, like WLD. Consider that the side channels that allow for water and sediment to enter island interiors (Figure 1a, inset) are important for sediment and water exchange between channels and islands and may be the result of patch-scale feedback (Piliouras & Kim, 2019;Wright et al, 2018). Hence, the patch-scale feedback that creates channels and connectivity counterbalances the buffering effect that limits flow onto the islands.…”
Section: Modeling Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This patch-scale feedback may strongly influence sediment retention on deltas, like WLD. Consider that the side channels that allow for water and sediment to enter island interiors (Figure 1a, inset) are important for sediment and water exchange between channels and islands and may be the result of patch-scale feedback (Piliouras & Kim, 2019;Wright et al, 2018). Hence, the patch-scale feedback that creates channels and connectivity counterbalances the buffering effect that limits flow onto the islands.…”
Section: Modeling Study Limitationsmentioning
confidence: 99%
“…Previous work has shown that dense vegetation enhances sediment deposition and retention in both salt marshes and deltaic freshwater marshes by decreasing water flow velocities, enhancing bed roughness and shear strength, and directly capturing sediment in the vegetation canopy (Chen et al, 2012;Christiansen et al, 2000;Fagherazzi et al, 2012;Gedan et al, 2011;Larsen, 2019;Leonard & Luther, 1995;Lightbody & Nepf, 2006;Ma et al, 2018;Nepf, 1999;Nepf, 2012aNepf, , 2012bNeumeier & Ciavola, 2004;Tanino & Nepf, 2008;Zong & Nepf, 2010). However, in some instances, vegetation also has been shown to divert flow away from patches of densely vegetated area, resulting in reduced sediment deposition within these patches and increased erosion along their edges due to locally enhanced flow velocities (Chen et al, 2012;Nardin et al, 2016;Nardin & Edmonds, 2014;Nepf, 1999;Nepf, 2012aNepf, , 2012bPiliouras & Kim, 2019;Temmerman et al, 2005Temmerman et al, , 2007Van Dijk et al, 2013;Zong & Nepf, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The timing and magnitude of this transition are strongly controlled by external drivers and the extent and density of vegetation coverage. Previous work shows that vegetation patterns can significantly influence flow and sediment in wetlands (Ma et al., 2018; Piliouras & Kim, 2019; Piliouras et al., 2017; Wright et al., 2018) and are linked to insights into nitrate removal (Knights et al., 2020), making vegetation a driving mechanism on transitions in hydrological and biogeochemical process connections.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has pointed to the importance of patchy vegetation in creating flow variability that can lead to channelization. Numerical experiments show patches of sufficient size and density concentrate flow between them leading to erosion, and channelization (Yamasaki et al, 2019), a process which may create and maintain the secondary channels on the islands of WLD (Piliouras & Kim, 2019;Wright et al, 2018). Future work would benefit from looking at how patchy vegetation influences the patterns of sediment deposition, and whether this is more important than the contrasting effects of rivers and tides described in Figure 8.…”
Section: Contrasting Effect Of Floods and Tides On Sediment Deposition Patterns With And Without Vegetationmentioning
confidence: 99%